The spectrum of Ge VII in the range 100 – 130 Å. (June 2022) - Ryabtsev, A.N.
Highlights: High resolution spectrum of germanium excited in a vacuum spark was studied below 130 Å. Transitions from 3d 7 4f and 3d 7 5f configurations in Ge VII are identified. New energy levels are derived from identified Ge VII wavelengths. Configuration interaction calculations are performed for interpretation of the Ge VII spectrum. Abstract: The spectrum of the Ge +6 ion recorded with high resolution was studied in the range 100 - 130 Å. The 3d 8 – 3d 7 (4f +5f) transitions were analyzed resulting in the identification of 144 and 11 spectral lines of transitions from 84 levels of the 3d 7 4f configuration and 13 ones of the 3d 7 5f configuration, correspondingly.